Screen Fatigue During Online Learning Among First Grade of Nursing Students - Yosep, Iyus; Sakti, Dimas Wibawa; Mardhiyah, Ai; Maulana, Indra; Hernawaty, Taty; Lukman, Mamat (STIKep PPNI Jawa Barat, 2024)
Aims: Online learning causes mental health problems in students. Fatigue among students can hinder concentration, memory retention, and cognitive functioning, leading to decreased academic productivity, heightened stress, and disrupted personal and social lives. Screen fatigue among students can be attributed to factors such as prolonged screen exposure, inadequate breaks, poor ergonomics, multitasking, content nature, sleep deprivation, screen brightness, glare, visual discomfort, and reduced physical interaction during online classes. Method: This study used a quantitative descriptive design. The population in this study were first-year nursing students during online learning. The sample technique used total sampling. The sample in this study amounted to 180 respondents. Data collection used the Zoom Exhaustion & Fatigue Scale (ZEF Scale). Univariate data analysis to describe the frequency of screen fatigue levels in students. Results: The results of this study indicate that the majority of students have a moderate level of screen fatigue, namely 77 respondents (42.8%). Then respondents with low screen fatigue category were 45 people (25%). Then respondents with high screen fatigue category were 58 people (32.2%). This shows that student screen fatigue is still high, so lecturers and students must care about each other's mental health problems during online learning. Conclusion: Screen fatigue is a problem experienced by students during online learning, this data becomes data for universities to develop learning methods that are effective in reducing the problem of screen fatigue in students. Nursing Implications: The implication of this research is that there is data for universities and lecturers in providing psychological services to students during online learning.